1988
DOI: 10.1016/0014-5793(88)80861-5
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of D‐glyceraldehyde‐3‐phosphate dehydrogenase by Ca2+/calmodulin‐dependent protein kinase II

Abstract: Rabbit muscle D-glyceraldehyde-3-phosphate dehydrogenase was shown to serve as a substrate for Ca*+/calmodulindependent protein kinase II with a K,,, of 0.33 PM and a V,,,,, of 2.63 pmol.min-i.rng-i at pH 7.5 and 30°C. In the absence of calmodulin, the V,,, was halved and K,,, unchanged. 0.99 mol of phosphate was incorporated per tetrameric molecule of D-glyceraldehyde-3-phosphate dehydrogenase under the experimental conditions employed.Phosphorylation; D-Glyceraldehyde-3-phosphate dehydrogenase; Ca2+/calmodul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…Considering the basic change in pI, it may be reasonable to suggest phosphorylation as this post-translational modification. This would be in accord with previously described GAPDH phosphorylation by protein kinases [Reiss et al, 1986;Ashmarina et al, 1988;Tisdale, 2002] or by its autophosphorylation [Kawamoto and Caswell, 1986]. Irrespective of the specific post-translational modification, a further support for this control mechanism is the defined cell cycle regulation of GAPDH subcellular localization defined in these new studies (Table I) and in previous investigations [Schmitz, 2001;Corbin Gong et al, 2002].…”
Section: Discussionsupporting
confidence: 83%
“…Considering the basic change in pI, it may be reasonable to suggest phosphorylation as this post-translational modification. This would be in accord with previously described GAPDH phosphorylation by protein kinases [Reiss et al, 1986;Ashmarina et al, 1988;Tisdale, 2002] or by its autophosphorylation [Kawamoto and Caswell, 1986]. Irrespective of the specific post-translational modification, a further support for this control mechanism is the defined cell cycle regulation of GAPDH subcellular localization defined in these new studies (Table I) and in previous investigations [Schmitz, 2001;Corbin Gong et al, 2002].…”
Section: Discussionsupporting
confidence: 83%
“…Our observation that GAPDH is an in situ substrate for PhK was not completely surprising, given that once before it had been reported that under unspecified in vitro conditions a small amount of phosphate was incorporated into purified GAPDH by PhK (48). Prior to that, the EGF receptor tyrosine kinase had been shown to phosphorylate GAPDH in vitro to relatively high yields (49).…”
Section: Discussionmentioning
confidence: 96%
“…It is possible that either site or both can be phosphorylated also by other kinases such as casein kinase II or Ca 2ϩ / camodulin-dependent protein kinase II (34,35), although the exact amino acid modified by them is unknown. Nonetheless, Thr-246 substituted by alanine (T246A) was sufficient to abolish PKC␦-mediated inhibition of mitophagy during I/R-induced injury, which coincided with a reduction in mitochondrial mass.…”
Section: Discussionmentioning
confidence: 99%